On the frontline treating COVID‐19: A pendulum experience—from meaningful to overwhelming—for Danish healthcare professionals. Issue 23 (26th July 2021) - Rosted, Elizabeth; Thomsen, Thora Grothe; Krogsgaard, Marianne; Busk, Henriette; Geisler, Anja; Thestrup Hansen, Stine; Kjerholt, Mette; Mortensen, Camilla Becker; Thomsen, Trine Hørmann; Beck, Malene; Petersen, Marian
Abstract: Objectives: In the current study, we aimed to explore the experiences and attitudes among healthcare professionals as they transitioned from their familiar disciplines to respiratory medicine, intensive care or other departments during the first wave of the COVID‐19 pandemic. Background: In preparation for the increasing number of patients suspected of having or who would be severely ill from COVID‐19, a major reconstruction of the Danish Healthcare System was initiated. The capacity of the healthcare system to respond to the unprecedented situation was dependent on healthcare professionals' willingness and ability to engage in these new circumstances. For some, this may have resulted in uncertainty, anxiety and fear. Design: The study was a descriptive study using semi‐structured focus group interviews. Healthcare professionals ( n = 62) from seven departments were included, and 11 focus group interviews were conducted. The focus group interviews took place during June 2020. Analyses was conducted using thematic analysis. The current study was reported using the consolidated criteria for reporting Qualitative research (COREQ). Results: Healthcare professionals experiences was described by five themes: 1) Voluntary involvement, 2) Changes within the organisation, 3) Risks, 4) Professional identity and 5) Personal investment. Common to all five themes was the feeling of being on a pendulum from a meaningful experience to an experience of mental overload, when situations and decisions no longer seemed to be worthwhile. Conclusions: Healthcare professionals experienced a pendulum between a meaningful experience and one of mental overload during the COVID‐19 pandemic. The swinging was conditioned by the prevailing context and was unavoidable. Relevance to clinical practice. To balance the continuous pendulum swing, leaders must consider involvement, and to be supportive and appreciative in their leader style. This is consistent with a person‐centred leadership that facilitates a well‐adjusted work‐life balance and may help prevent mental overload developing into burnout.